Review of studies on oral case presentations in clinical settings - Mahmud, Nur Farah Fadhliah; Mohamad Ali, Afida; Chan, Mei Yuit (Malaysian Association of Modern Languages, 2014)
Recent years have evidently shown that genre studies are growing considerably in language studies, mainly in the study of academic and professional genre. A number of academic genres have been focusing on the analysis of structural elements in research articles and theses’ introduction. However, very few studies have attempted to examine the structural elements in professional genres, especially in medical academic setting. Due to the importance of this professional genre, particularly towards novices in order to improve their communication skills in presenting medical cases to their instructors or superiors, this paper reviews past studies related to genre analysis of oral case presentations in their academic and professional settings. By doing so, it reaches the conclusion that there are generic elements in oral case presentations that can guide medical novices to improve their way of presenting case presentations in medical academic settings.